Exploring stakeholders’ ecosystem services perceptions across Massachusetts Bays using deliberative valuation - Lyon-Mackie, Jennifer; Vella, Prassede; DiBona, Pamela A.; Shehab-Sehovic, Noora; Roche, Samantha B.; Kreiley, Allison I.; Mavrommati, Georgia (Frontiers in Environmental Science, 2023)
Deliberative methods to assess ecosystem services values formalize community members' and stakeholders' involvement in decision-making related to natural resources management. This paper presents the methodological design and the application of a deliberative multicriteria evaluation (DMCE) method that combines the advantages of deliberation with structured decision-making to assess community-based values of four coastal ecosystem services (valued by indicators such as Total Nitrogen, Blue Carbon, Scallop Landings, Fish Abundance) and explore the spatial variability of group values along the Massachusetts coastline. We implemented four virtual deliberative workshops consisting of stakeholders from four Massachusetts Bays (MassBays) estuarine categorizations to collect quantitative and qualitative data. Quantitative data came from individual survey results and group preferences, while qualitative data were derived through the analysis of video recordings and transcripts of deliberations. Compared to previous studies, we combined quantitative and qualitative data by using applied thematic and co-occurrence analysis to identify themes of discussion during the deliberative process. Our results show that coastal stakeholders place a particular emphasis on access to clean water and services that directly support human wellbeing and provide direct economic benefits. Differences in the quantitative and qualitative results of these deliberative tasks between groups provide insight into the need for localized policymaking instead of solely regional or statewide management. Environmental managers and policymakers will utilize these insights to address local values and priorities as they work towards implementing habitat restoration efforts.